OPTIMALISASI PEMBINAAN UNTUK MENINGKATKAN DISIPLIN GURU DALAM MENGAJAR DI SMP NEGERI 2 KUBU BABUSSALAM KABUPATEN ROKAN HILIR - Baharuddin Baharuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This study aims to improve teacher discipline in teaching by optimizing the guidance of teachers at SMP Negeri 2 Babussalam. This research is a school action research (PTS) which aims to increase the role of teachers in the teaching and learning process. The subjects in this study consisted of 26 teachers of SMP Negeri 2 Kubu Babussalam. The results showed that the action of optimizing the guidance of teachers can improve discipline and teacher performance in teaching, it can be seen from the percentage of teacher discipline after reflection is obtained by 83%, an increase compared to the initial data of only 58%, the increase in teacher activity can also be seen from the observation analysis Teacher activities obtained by a percentage of 85%, there was an increase compared to the initial data of only 65%, because it can be concluded that the implementation of coaching can improve teacher discipline in teaching at SMP Negeri 2 Kubu Babussalam Rokan Hilir.